(untitled) (Bangladesh Journal of Botany, 2024)
Cape gooseberry is a nutrient loving crop. But excessive use of inorganic fertilizers may leads to health hazards, ecological vulnerabilities and diminution of soil physico-chemical characteristics. Hence, a trial was conducted for substituting inorganic fertilizers with biofertilizer in cape gooseberry to maintain the yield potential with soil fertility status too. The experimental plants were treated with azotobacter, phosphate and potash solubilizing bacteria (PSB and KSB) at 10 g plant-1 each with reduced dose of recommended fertilizer (RDF) (100- 60%) for two consecutive growing season. Total harvestable fruit plant-1 with highest yield was recorded in 90% RDF + Azotobacter, PSB and KSB treatment with par value in 60% RDF + Azotobacter, PSB and KSB treatment. Quality of ripped fruit with respect to TSS (15.90 °B), total sugar (11.29%), ascorbic acid (60.03 mg 100 g-1) and carotenoid content (49.25 µg 100 g-1) was also improved significantly in 60% RDF + Azotobacter, PSB and KSB treatment. Soil physico-chemical properties of the field was not varied significantly over initial reading. However, microbial population viz. bacteria, fungi and actinomycetes count was improved significantly in all the nutrient modules. Hence, it can be concluded that integrated nutrient module comprising 60% RDF of NPK + Azotobacter, PSB and KSB at 10 g plant-1 is the best treatment module for improving the production system of cape gooseberry in sustainable manner for long run without hampering the soil health and quality. Bangladesh J. Bot. 53(1): 83-90, 2024 (March)